Using Geochemical Fingerprints for Assessing Sediment Source Apportionment in an Agricultural Catchment in Central Argentina - Garcias Paez, Yanina Vanesa (2021)
In the hilly semi-arid region of central Argentina, where the agricultural frontier expands at the expense of natural ecosystems, soil erosion is one of the most alarming environmental problems. Thus, obtaining knowledge about the dynamics of erosive processes and identifying erosion hotspots constitutes a primary scientific objective. This investigation is focused on estimating the apportion-ments of main sources of sediments, at the mouth of a small catchment called Durazno del Medio, located in the province of San Luis, Argentina. Elemental Analysis, measured by Energy Dispersive X-ray Fluorescence (EDXRF), was used to select potential geochemical fingerprints of sediment. The unmixing model MixSIAR was applied to approximate the contribution of each identified source in the sediment accumulation areas at the mouth of the catchment. Potential sediment sources were selected using two criteria: (i) a hierarchical approach to identify the main geomorphological units (GUs) and (ii) the main land uses (LU), recognized by examining satellite images and field recogni-tions. The selected geochemical tracers were able to distinguish sources located in the Crystalline basement hills with loess-patched (CBH) as the main sediment contributors.